How Do Australians Manage Diagnostic Testing Risks? Focus Groups Linked to a Model of Behaviour Change - Rozbroj, Tomas; Parker, Catriona; Haas, Romi; Wallis, Jason A.; Buchbinder, Rachelle; O'Connor, Denise A. (Health expectations : an international journal of public participation in health care and health policy, 2024)
ABSTRACT Background Diagnostic tests carry significant risks, and communications are needed to help lay people consider these. The development of communications has been hindered by poor knowledge about how lay people understand and negotiate testing risks. We examined lay Australians' perceptions of diagnostic testing risks and how these risks are managed. Method We completed 12 semistructured online focus groups with 61 Australian adults (18+) between April and June 2022. Participants were divided into younger/older (> 50 years) and male/female groups. Using semistructured discussion and exploring two hypothetical scenarios, we examined attitudes to diagnostic tests, their risks and how test risks were managed. Themes were identified, subanalysed to identify age and gender differences and mapped to the COM‐B model of behaviour change. Results The six themes provided detailed accounts of how participants considered themselves able, empowered and assertive when negotiating testing risks and of complex ways in which relationships with health workers, personal experiences and structural factors influenced negotiating testing risks. COM‐B identified multiple opportunities for leveraging these lay beliefs in health promotion. It also identified barriers, including narrow concepts of testing risks, challenges during shared decision‐making and overestimation of personal influence on testing decisions. Significance Our findings matter because they are a novel, detailed account of testing risk beliefs, linked to a model for behaviour change. This will directly inform development of test risk/benefit communications, which are a research priority. Public Contribution The study design enabled participants to influence the discussion agenda, and they could comment on the analysis. Participants contributed insights about their needs, beliefs and experiences related to medical testing, and these will be used to shape future patient‐centred decision tools.